(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article considers distance education that requires rethinking and modernization of existing methods of teaching the educational process that have developed in the contact-classroom environment. Opportunities, advantages and disadvantages of online education, and prospects for applying joint traditional and distance education.